Post-COVID gambling habits of adolescents and young adults in Aragon, Spain: a cross-sectional study - Alberto Barceló-Soler; Carilene Armas-Landaeta; Adrián Pérez-Aranda; Alicia Monreal-Bartolomé; María Beltrán-Ruiz; Itxaso Cabrera-Gil; Loreto Camarero-Grados; Javier García-Campayo; Yolanda López-del-Hoyo (BMC Public Health)
Abstract Background Gambling has become increasingly normalized in Spain, with 49.3% of the population participating and high engagement among youth, particularly online. Despite legal restrictions, some studies have reported that over 20% of adolescents aged 14–19 reported gambling in 2022. These findings raise concerns about gambling disorder, which affects 4.7% of Spanish youth and is linked to other mental health problems. Factors such as advertising and the COVID-19 pandemic may have contributed to this trend. This study, part of the GAMBL-OUT project, examines gambling behaviors among young people in Aragon, Spain, focusing on prevalence, advertising exposure, post-COVID vs. pre-pandemic comparisons, and factors associated with problem gambling, while comparing high school and university students. Methods A cross-sectional study was conducted between November 2023 and March 2024 with 617 participants aged 16–25 from high schools, vocational centers, and universities. Measures included sociodemographic variables, gambling behaviors, advertising exposure, and psychological constructs. Standardized tools included the Problem Gambling Severity Index, Gambling Related Cognitions Scale, Gambling Motives Questionnaire, and UPPS-P Impulsive Behavior Scale. Results Nearly 60% of participants had gambled, 78.4% of whom had done so in the past 12 months. The overall prevalence of problem gambling in our sample was 3.5%. Among university students, 64.6% had gambled and 3.4% showed signs of problem gambling, which does not represent a significant increase compared to 2019 data. University students post-COVID reported significantly lower exposure to gambling advertisements and less knowledge of betting venues and websites, despite stable levels of preventive information. Although lifetime gambling increased (65.3% vs. 58.1%), riskier behaviors such as sports betting, online gambling, and microtransactions decreased. University students showed greater gambling participation and online awareness, while high school students showed higher impulsivity and stronger gambling intentions. Regression analyses identified enhancement motives, predictive control, negative urgency, and peer influence as factors associated with problem gambling. Conclusions Gambling remains a prevalent issue among youth in Aragon, with problem gambling rates stable over time. Despite reduced advertising exposure, the normalization of gambling persists. Findings support the need for age-specific, psychologically informed interventions addressing both individual vulnerabilities and social contexts.